Characterization and Analysis of the Mortars of the Church of San Francisco of Quito (Ecuador) - M. Lenin Lara Calderón; Inés del Pino; Sol López-Andrés; David Sanz-Arauz (Heritage, 2023)
The relevance of the Franciscan community is reflected in the San Francisco church in Quito, which was built between 1535 and 1755. This architectural work belonging to the Franciscan complex was implanted on a plot of land with an area of 3.5 hectares and was one of the first buildings in the Audience of Quito. Eleven mortar samples that covered the walls of the central nave and side chapels were taken from the church’s main temple. The procedure proposed by the authors is based on a combined methodology following the standards and protocols for the less-invasive extraction of heritage samples. Tests included X-ray diffraction, petrography, and scanning electron microscopy with a microanalysis of the samples. Mortars with a rustic composition and rough manufacturing were identified to differentiate two types of mortar, one of earthen with volcanic aggregates and another of lime with volcanic aggregates. The mining data validated the existing historical documentation, the imaginary process, and the stages of the established constructions.